Rare Prenatal Association of complete Trisomy 15 with 69, XXX Triploidy: Case Report and Literature Review - Bacha , Dhouha; Battikh, Rania; Beltaifa , Dorsaf; Halouani , Ahmed; Ben Slama , Sana; Lahmar , Ahlem (Biomedicine & Healthcare Research, 2026)
Background: Trisomy 15 and triploidy are both rare chromosomal abnormalities usually observed in early pregnancy losses. Their coexistence in a viable gestation has never been reported. This case describes an exceptional prenatal association of complete trisomy 15 and 69XXX triploidy, providing detailed clinical, sonographic, and cytogenetic documentation. Case presentation: A 41‑year‑old pregnant woman underwent a second‑trimester morphology ultrasound showing severe, proportionate fetal growth restriction, absent nasal bones, and clenched hands. Amniocentesis at 26 weeks identified 69, XXX by FISH, and conventional karyotyping subsequently revealed complete trisomy 15. Multidisciplinary counseling led to termination at 29 weeks. Postmortem examination confirmed a female phenotype with craniofacial dysmorphia (flat forehead, mild nasal flaring, hypertelorism, retrognathism), elongated limbs with clenched hands, and a bulging thorax, without visceral or cerebral malformations. Conclusions: This case illustrates an exceptionally uncommon combination of numerical chromosomal abnormalities. Although isolated trisomy 15 and triploidy can each present with growth restriction and multiple abnormalities, their co‑occurrence likely confers near‑certain lethality. Early detailed ultrasound followed by definitive cytogenetic testing is critical for counseling and management in suspected multiple aneuploidies.